2023
DOI: 10.1371/journal.pone.0282871
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of COVID-19 vaccine hesitancy among students and parents in Sentinel Schools Network of Catalonia, Spain

Abstract: Vaccine hesitancy is defined as a delay in acceptance of vaccines despite its availability, caused by many determinants. Our study presents the key reasons, determinants and characteristics associated with COVID-19 vaccine acceptability among students over 16 years and parents of students under 16 years and describe the COVID-19 vaccination among students in the settings of sentinel schools of Catalonia, Spain. This is a cross-sectional study that includes 3,383 students and the parents between October 2021 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
3
2
0
Order By: Relevance
“…Majority of the participants reported concerns about side effects resulting from the COVID-19 vaccines. This finding is in line with studies conducted in Uganda and Spain [ 26 , 45 ]. Besides that, our findings also revealed that vaccines were not liked and that these vaccines could instead infect them with COVID-19 virus.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Majority of the participants reported concerns about side effects resulting from the COVID-19 vaccines. This finding is in line with studies conducted in Uganda and Spain [ 26 , 45 ]. Besides that, our findings also revealed that vaccines were not liked and that these vaccines could instead infect them with COVID-19 virus.…”
Section: Discussionsupporting
confidence: 93%
“…However, this systematic review did not only include a single Ugandan study [ 25 ], but also, the said study focused on medical students leaving out the bigger population which this study addresses. The other reasons for vaccine hesitancy include; COVID-19 is not a serious illness, costs associated with the vaccine (such as office visit costs or vaccine administration fees) and distrust in COVID-19 vaccines [ 26 28 ]. However, many of these studies have been conducted in high income countries like Spain, Malaysia and USA which may not be a true representation of Uganda.…”
Section: Introductionmentioning
confidence: 99%
“…We examined some of the reasons why there is hesitation or refusal to receive COVID-19 vaccine among persons aged 13-80 years and majority of the participants had concerns about side effects resulting from the vaccines. These findings are consistent by a study conducted in Sentinel Schools Network of Catalonia, Spain conducted among students and parents (10). Besides our findings also revealed that vaccines were not liked and that these vaccines could infect them with the Corona virus.…”
Section: Discussionsupporting
confidence: 92%
“…There are different reasons for why some people hesitate or refuse to receive COVID-19 vaccine as described elsewhere and these include; fear of side effects, vaccines not being effective, don't like vaccines, COVID-19 is not a serious illness, Concern about the costs associated with the vaccine (such as office visit costs or vaccine administration fees), distrust in vaccines (10,11) adults (12). However, many of these studies have been conducted in high income countries and among students for example Spain, Malaysia with limited urban population-based studies in Sub-Saharan Africa more especially Uganda (Wakiso) among persons aged 13-80 years.…”
Section: Introductionmentioning
confidence: 99%
“…Different sources of information had an in uence on increasing vaccine hesitance similar to the ndings of Osuagwu et al, [53], who found that all six information sources such as social media, television, health workers, family, and friends were strongly associated with vaccine hesitance in sub-Saharan African countries, except radio was not a strong predictor. The ndings are also similar to those of Ganem et al, [54] in the USA who found that the key reason to not vaccinate themselves, or their children, were concern about side effects, insu cient research about the effect of the vaccine in children, the rapid development of vaccines, the necessity for more information and previous infection by COVID-19.…”
Section: Discussionsupporting
confidence: 86%